2019
DOI: 10.1002/cpp.2410
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the clinical significance of treatment outcomes for distressing voices in routine clinical practice

Abstract: Determining reliable and clinically significant change is central to evidence-based practice yet rarely used in routine clinical settings. This paper illustrates these methods in the context of an evaluation of cognitive behaviour therapy for distressing auditory hallucinations ("voices"). We used data from a clinical sample attending Perth Voices Clinic, a transdiagnostic outpatient service for distressing voices, and a previously published reference sample of healthy voice hearers. Our outcomes on the primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Furthermore, these outcomes can be viewed from varying perspectives, each of which may seem to tell a slightly different story as: the majority of patients reported an improvement on the primary outcome (71%); about half experienced a treatment response in the minimum improvement category (51%); and reliable change was demonstrated by only a minority (29%). These varying perspectives are reflective of the ongoing debate within the field about which outcomes to measure (Thomas et al, 2014) and how they should be measured (Badcock et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these outcomes can be viewed from varying perspectives, each of which may seem to tell a slightly different story as: the majority of patients reported an improvement on the primary outcome (71%); about half experienced a treatment response in the minimum improvement category (51%); and reliable change was demonstrated by only a minority (29%). These varying perspectives are reflective of the ongoing debate within the field about which outcomes to measure (Thomas et al, 2014) and how they should be measured (Badcock et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The subscales used in this study have demonstrated good reliability (intra‐class correlation coefficient > .93 for distress and > .87 for frequency) (Woodward et al, 2014 ), and they have been used in adult (e.g. Badcock et al, 2020 ; Craig et al, 2018 ; du Sert et al, 2018 ; Hayward et al, 2017 , 2018 ; Jongeneel et al, 2018 ; Lincoln et al, 2021 ; Paulik et al, 2019 , 2018 ) and youth research (Cavelti et al, 2019 ). In this study, internal consistency of PSYRATS‐AH subscales was acceptable (α > .66).…”
Section: Methodsmentioning
confidence: 90%
“…To understand if the treatments were effective, the sessional score changes were checked to see if they showed improvement over time. In addition, a reliable change index (RCI) was calculated for the SDQi and the BPSES (Badcock et al., 2020) (Evans et al., 1998) to understand the importance of any change. The SDQi, GBOs and the BPSES items were restructured to a vertical format.…”
Section: Methodsmentioning
confidence: 99%